2012
DOI: 10.1029/2012ja017797
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of chorus waves and their source electrons during storms driven by corotating interaction regions

Abstract: [1] During Corotating Interaction Region (CIR)-driven storms, relativistic electron fluxes in the outer radiation belt decrease in the main phase, followed by a gradual increase in the recovery phase. Recent studies have shown that whistler mode chorus waves play an important role in accelerating the seed electron population to relativistic energies in the outer radiation belt. However, the evolution of chorus waves and their source electrons responsible for the wave excitation during storm various phases is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 105 publications
1
22
0
Order By: Relevance
“…The CIR storms in this study do not show a larger recovery phase Kp, so it is not surprising that while the results here agree with those of Spasojevic (2014) during the main phase, they do not show the same recovery phase feature. The results of this study show that the measured chorus wave activity and the source electron population along with the corresponding chorus wave growth proxy are most enhanced during the main phase in the inner magnetosphere between L = 3-6, matching the results from Li et al (2012) and Spasojevic (2014), and that while the results here do not directly match those by MacDonald et al (2008MacDonald et al ( , 2010, the discrepancies can be explained by field line stretching outside of the chorus source region observed at geosynchronous orbit. Journal of Geophysical Research: Space Physics observations at South Pole Station showed a strong dropout in chorus activity and amplitude during the main phase.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The CIR storms in this study do not show a larger recovery phase Kp, so it is not surprising that while the results here agree with those of Spasojevic (2014) during the main phase, they do not show the same recovery phase feature. The results of this study show that the measured chorus wave activity and the source electron population along with the corresponding chorus wave growth proxy are most enhanced during the main phase in the inner magnetosphere between L = 3-6, matching the results from Li et al (2012) and Spasojevic (2014), and that while the results here do not directly match those by MacDonald et al (2008MacDonald et al ( , 2010, the discrepancies can be explained by field line stretching outside of the chorus source region observed at geosynchronous orbit. Journal of Geophysical Research: Space Physics observations at South Pole Station showed a strong dropout in chorus activity and amplitude during the main phase.…”
Section: Discussionsupporting
confidence: 60%
“…Spasojevic (2014) showed using Antarctic magnetometer data from 2000 to 2010 that CME-and CIR-driven storms had very little difference in chorus occurrence and amplitude with an exception of the half day after minimum Dst*, in which CIR storms had higher occurrence rates and higher average Kp. Li et al (2012) showed using THEMIS observations between L* = 5-9 that 10 MeV/G of source electrons were most enhanced around minimum Dst between L* = 5-9, while chorus activity was strongest then as well. Spasojevic (2014) also showed a storm intensity dependence on chorus amplitude and occurrence, as larger storms had more, stronger, and longer lasting chorus activity than moderate storms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This anisotropic population of ring current energy electrons is often called the "seed" population, wherein the source of the free energy for chorus wave growth is available. Chorus waves interact with "seed" electrons at energies of 10's to 100's of keV through cyclotron resonance and can accelerate electrons to very high energies (Kennel and Petschek 1966;Kennel and Thorne 1967;Li et al 2008Li et al , 2012Thorne 2010). Whistler-mode chorus plays a critical role in accelerating ring current electrons to relativistic energies in the outer belt (Horne et al 2005;Green 2006;Chen et al 2007), including to "killer" electron energies that can have disastrous space weather consequences to sensitive systems (Baker 2001;Fennell et al 2001).…”
Section: Ring Current and Radiation Beltsmentioning
confidence: 99%
“…Lyons et al [2005] indicated that the enhancement of both relativistic electrons and the whistler mode waves that drive the electron acceleration processes are associated with the enhanced convection driven by Alfvenic fluctuations within an HSS. More recently, Li et al [2012] showed a superposed epoch analysis of chorus waves and hot electrons about CIR-driven storms using Time History of Events and Macroscale Interactions during Substorms data. The evolutions of chorus wave activity and source electron population depend greatly on the preceding IMF-Bz orientation.…”
Section: Introductionmentioning
confidence: 99%